Improving the Quality of Learning through Supervision by the School’s Principal - Patraliza, Hellen (PPSDP International Journal of Education, 2023)
The goal of this study is to evaluate initiatives to raise learning quality by implementing academic principal supervision. At SMA Negeri 3 Kayuagung, this study was conducted. using interviews, documentation, and observation as data collecting methods. ways for analyzing data utilizing descriptive qualitative analysis. According to the study’s findings, the academic oversight provided by SMA Negeri 3 Kayuagung’s principal has been working well to improve teachers’ capacity to carry out instructional tasks, particularly preparing the administration of instructional tools, planning instructional activities, carrying out instructional activities, managing classes, and conducting instructional evaluations. The quality of instruction at SMA Negeri 3 Kayuagung is improved through the implementation of the principal’s academic supervision.